Heavy Metal (Cu, Co, Mn, Pb) Uptake and Health Risk Associated with Medicinal Plants from different Contrasting Locations - Arfa Raza; Sajida Shabbir; Bushra Huma; Mahrukh Mumtaz; Niaz Hussain; Mian Jahan Zaib Rasheed (Dialogue Social Science Review (DSSR), 2025)
This study explored the accumulation of copper (Cu), cobalt (Co), manganese (Mn), and lead (Pb) in soils and commonly used medicinal plants from two distinct locations and eight different sites. Metal uptake was assessed through Bioconcentration Factor (BCF), whereas health risks were evaluated using Daily Intake of Metals (DIM) in eight different medicinal plants. Cu levels in plants were high, especially in Adhatoda vasica, with BCFs reaching up to 10.78. Co showed the least uptake with BCFs below 0.13. Mn concentrations, although below toxic limits, had considerable BCFs, indicating active absorption. Pb accumulation was moderate but still raised concern due to its toxicity and presence in several plant species. The DIM values suggest that continued, unregulated use of these plants could pose health risks, particularly from Cu and Mn exposure. Overall, the results point to significant variability in metal accumulation across plant species and locations, emphasizing the importance of site-specific monitoring to ensure the safe use of medicinal plants. Future studies should include a wider range of heavy metals (e.g., Cd, Zn, Cr) and assess seasonal variations in metal uptake to build a more comprehensive understanding of risks. Keywords: Pothohar, medicinal plants, heavy metals, dietary risk assessment, toxicity https://doi.org/10.5281/zenodo.16739146